Near-IR TRGB Distance Modulus of Dwarf Irregular Galaxy IC 1613 - M. Y. Jung; S.-H. Chun; C.-R. Chang; M. Han; D. Lim; W. Han; Y.-J. Sohn (Journal of Astronomy and Space Sciences, 2009)
The JHKs magnitudes of the red giant branch tip (TRGB) and the distance moduli of the nearby dwarf irregular galaxy IC 1613 have been determined from the nearinfrared luminosity functions (LFs) of the resolved stars in the galaxy. Applying a Savitzky-Golay filtering, we derived the second derivatives of the LFs, and estimated the apparent magnitudes of the TRGB as mJ = 19.1, mH = 18.4, and mKs = 18:0. The mean values of the theoretical absolute magnitudes of the TRGB were measured by using the Yonsei-Yale isochrones with a metallicity range of -2.1 < [Fe/H] < -0.5 and age of 12 Gyr. The derived values of near-infrared TRGB distance moduli for IC 1613 are (m-M) = 24.12±0:25, 24.20±0.44, and 24.00±0.52 for J;H, and Ks bands, respectively.